IL2RA Methylation and Gene Expression in Relation to the Multiple Sclerosis-Associated Gene Variant rs2104286 and Soluble IL-2Rα in CD8+ T Cells - Buhelt, Sophie; Laigaard, Hannah-Marie; von Essen, Marina Rode; Ullum, Henrik; Oturai, Annette; Sellebjerg, Finn; Søndergaard, Helle Bach (Frontiers in Immunology, 2021)
CD8+ T cells are involved in the pathogenesis of multiple sclerosis (MS). The interleukin-2 receptor α (IL-2Rα) is important for CD8+ T cell function, and single nucleotide polymorphisms (SNPs) in the IL2RA gene encoding IL-2Rα increase the risk of MS. Therefore, in isolated CD8+ T cells we investigated IL2RA gene methylation and gene expression in relation to the MS-associated IL2RA SNP rs2104286 and soluble IL-2Rα (sIL-2Rα). We have identified allele specific methylation of the CpG-site located in intron 1 that is perturbed by the rs2104286 SNP in CD8+ T cells from genotype-selected healthy subjects (HS). However, methylation of selected CpG-sites in the promotor or 5’UTR region of the IL2RA gene was neither associated with the rs2104286 SNP nor significantly correlated with IL2RA gene expression in HS. In CD8+ T cells from HS, we explored expression of immune relevant genes but observed only few associations with the rs2104286 SNP. However, we found that sIL-2Rα correlated negatively with expression of 55 immune relevant genes, including the IL-7 receptor gene, with Spearman’s rho between -0.49 and -0.32. Additionally, in HS by use of flow cytometry we observed that the IL-7 receptor on naïve CD8+ T cells correlated negatively with sIL-2Rα and was downregulated in carriers of the rs2104286 MS-associated risk genotype. Collectively, our study of resting CD8+ T cells indicates that the rs2104286 SNP has a minor effect and sIL-2Rα may negatively regulate the CD8+ T cell response.